Analisis Biaya dan Produktivitas Produksi Kayu Pada Hutan Tanaman Industri (Studi Kasus: PT. Sumatera Riang Lestari-Blok I Sei Kebaro, Kabupaten Labuhanbatu Selatan dan Kabupaten Padang Lawas Utara) - Warsein Roy M. Sitohang; Muhdi Muhdi; Yunus Afifuddin (Peronema Forestry Science Journal, 2016)
Analysis of costs and productivity of timber production is done in PT. Sumatera Riang Lestari. This research was conducted since August 2014 until September 2014. The purpose of this research is to analyze the cost of harvesting that focus on the stages of harvesting, the division of the stem, stacking, stripping, extraction, loading and analyzing productivity and harvesting of timber in HTI PT. Sumatera Riang Lestari. The method of analysis in the sampling trees is done by purposive sampling. To analyze the cost of harvesting used calculation formulas fixed costs and variable costs (variable). To analyze the productivity of harvesting is done by calculating the productivity of timber extraction from the location of HTI to sawmills with conveyances (truck). Data in the calculation of costs and productivity of timber harvesting obtained by direct observationin the field. The research results showed that the cost of harvesting, fixed and variable costs (variable) used is IDR 288.243/hour and IDR 398.849,38/hour. Productivity harvesting of timber obtained in plantation forests (HTI) PT. Sumatera Riang Lestari is 314,80 m3/day. Keyword: Cost Analysis, harvesting productivity, Industrial Plantation Forest, PT. Sumatera Riang Lestari.